Genetic diversity and population structure of fine aroma cacao (Theobroma cacao L.) from north Peru revealed by single nucleotide polymorphism (SNP) markers - Bustamante, Danilo E.; Motilal, Lambert A.; Calderon, Martha S.; Mahabir, Amrita; Oliva, Manuel (Frontiers in Ecology and Evolution, 2022)
Cacao (Theobroma cacao L.) is the basis of the lucrative confectionery industry with ‘fine or flavour’ cocoa attracting higher prices due to desired sensory and quality profiles. The Amazonas Region (north Peru) has a designation of origin, Fine Aroma Cacao, based on sensory quality, productivity and morphological descriptors but its genetic structure and ancestry is underexplored. We genotyped 143 Fine Aroma Cacao trees from northern Peru (Bagua, Condorcanqui, Jaén, Mariscal Cáceres, and Utcubamba; mainly Amazonas Region), using 192 single nucleotide polymorphic markers. Identity, group, principal coordinate, phylogenetic and ancestry analyses were conducted. There were nine pairs of matched trees giving 134 unique samples. The only match within 1838 reference cacao profiles was to a putative CCN 51 by a Condorcanqui sample. The ‘Peru Uniques’ group was closest to Nacional and Amelonado-Nacional genetic clusters based on FST analysis. The provinces of Bagua and Utcubamba were genetically identical (Dest = 0.001; P = 0.285) but differed from Condorcanqui (Dest = 0.016-0.026; P = 0.001-0.006). Sixty-five (49%) and 39 (29%) of the Peru Uniques were mixed from three and four genetic clusters respectively. There was a common and strong Nacional background with 104 individuals having at least 30% Nacional ancestry. The fine aroma of cacao from Northern Peru is likely due to the prevalent Nacional background with some contribution from Criollo. A core set of 53 trees was identified. These findings are used to support the continuance of the fine or flavour industry in Peru.